Bullying victimization and perpetration among adolescent sport teammates - Evans, B.; Adler, A.; MacDonald, D.; Côté, J. (Pediatric Exercise Science, 2016)
Purpose: Bullying is a specific pattern of repeated victimization explored with great frequency in school-based literature, but receiving little attention within sport. The current study explored the prevalence of bullying in sport, and examined whether bullying experiences were associated with perceptions about relationships with peers and coaches. Method: Adolescent sport team members (n = 359, 64% female) with an average age of 14.47 years (SD = 1.34) completed a pen-and-paper or online questionnaire assessing how frequently they perpetrated or were victimized by bullying during school and sport generally, as well as recent experiences with 16 bullying behaviors on their sport team. Participants also reported on relationships with their coach and teammates. Results: Bullying was less prevalent in sport compared with school, and occurred at a relatively low frequency overall. However, by identifying participants who reported experiencing one or more act of bullying on their team recently, results revealed that those victimized through bullying reported weaker connections with peers, whereas those perpetrating bullying only reported weaker coach relationships. Conclusion: With the underlying message that bullying may occur in adolescent sport through negative teammate interactions, sport researchers should build upon these findings to develop approaches to mitigate peer victimization in sport.